Habitat use by domestic reindeer in relation to food quality and disturbance - need for research? (In Swedish with Summary in English) - Skarpe, Christina; Halley, Duncan (Rangifer, 2005)
Competition for land in the mountains can be foreseen to increase in the near future. This development will result in trade offs and prioritization between the different demands for land. For reindeer husbandry it is essential to motivate the need for control over good grazing land for different seasons and situations, not only by preventing direct exploitation of such land, but also to minimize disturbance by traffic and people in the vicinity. It will therefore be important to demonstrate in quantitative terms 1) what habitat types and areas that are essential for the reindeer in different seasons and situations and for different activities (grazing, resting, protection for insects etc), and 2) how different forms and intensities of disturbance affect the reindeer. We plan a project with these aims and will primarily work with the summer grazing situation. For many years we have run a similar project related to sheep grazing in the vicinity of Hessdalen, and we have developed methods and techniques that to a large extent are applicable to reindeer. We will discuss methods and results from the sheep study, how they can apply to reindeer, and provide the quantitative information needed. We use modern, high resolution GPS telemetry with very high spatial resolution (95% within ca 6.4 m), and frequent recording, e.g., every five minutes during some periods. This provides knowledge not only of the movements by the animals in the landscape, but also on their activities and will be related to vegetation maps with the same accuracy as the telemetry data (from aerial photographs, offering higher resolution than available satellite data). Results show that sheep use only a very small portion of the available rangeland, and that selectivity varies with season and weather conditions. Almost certainly the situation is similar with reindeer, although the two species have rather different grazing pattern, with reindeer being much more mobile than sheep. We plan to use the same methods to describe what habitats and areas are essential for reindeer, and how it varies over time, with weather, insect abundance etc. The highly accurate telemetry also provides possibilities to quantify how different types and intensities of disturbance affects the habitat use and behavior of the different reindeer categories.